Insulin Knowledge, Handling, and Storage among Diabetic Pilgrims during the Hajj Mass Gathering - Saber Yezli; Yara Yassin; Abdulaziz Mushi; Bander Balkhi; Anas Khan (Journal of Diabetes Research)
Background. Diabetes is one of the most common underlying health conditions among Hajj pilgrims. Many diabetics manage their condition using insulin, which requires appropriate storage conditions to maintain its stability and effectiveness. We aimed to investigate insulin knowledge, storage, and handling among diabetic pilgrims during Hajj to identify specific areas for improvement. Method. Adult diabetic pilgrims from 22 countries were interviewed using a structured questionnaire during the 2019 Hajj. Results. The study enrolled 277 diabetic pilgrims with a mean age of 58.4 years (SD=10.4, range: 20-83) and male : female ratio of 1.6 : 1. Most participants (86.4%) were literate and reported using insulin for a mean of 7.1 years (SD=5.3, range: 1-23). Over 95% of pilgrims brought their insulin with them from their country of origin, where they also received most of their insulin storage information, mainly from physicians (77.8%) and pharmacists (59.6%). Pilgrims’ knowledge regarding insulin storage was just above average (mean knowledge score=0.51; SD=0.23). Pilgrims who were literate and previously received education on insulin storage, those with a higher level of education, and those with a longer duration of insulin therapy, had significantly higher knowledge scores. Pilgrims’ storage and handling of their insulin during Hajj also varied depending on the stages of their pilgrimage journey. Conclusion. Inadequate knowledge and inappropriate practices regarding insulin handling and storage were identified among diabetic Hajj pilgrims, which could compromise the quality of insulin and lead to health hazards. Improving diabetic pilgrims’ knowledge of diabetes management, including insulin storage, will be beneficial during the pilgrimage and beyond.